ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL-SOAL KESEBANGUNAN - Rahayu, Siti (JURNAL E-DUMATH, 2016)
The low studentâs learning achievement of mathematics becomes a greatchallenge for an educator. One of the causes of low student learningachievement caused difficulties to affect the student learning to theerrors of students in solving problems congruency. This study aims todetermine the percentage of the mistakes of the student that includesconceptual errors, fault principle, and operation errors in terms ofMinimum Completeness Criteria is 60 with the fault tolerance amaximum of 40%. The population was all of the students in third gradeof the SMP N Satu Atap 2 Negerikaton in the academic year 2014-2015.The samples of the research were taken by 50% from the population.Data acquisition is done by testing with data analysis techniques usingpercentages. Based on data analysis, it can be concluded that studentsmistakes in solving problems congruency include conceptual errors by57.60%, fault principle by 41.27%, and operation errors by 40.57%.With contributors biggest mistake is a conceptual errors.Keywords : conceptual errors, fault principle, operation errors